Pengaruh Suasana Restoran, Kualitas Pelayanan dan Gaya Hidup terhadap Kepuasan Pelanggan Panda Hotpot and Grill - Vendy Vendy; M. Khoiri (Universitas Batanghari, 2023)
The purpose of this research is to find out how the environment, food, and way of life at Panda Hotpot and Grill affect the happiness of its customers. The study sample size was 115 people, all of whom were randomly selected. Questionnaires were sent to collect information. Furthermore, SPSS version 25 is used to perform statistical analysis such as hypothesis testing, correlation analysis, multiple regression, and examination of classical assumptions and data quality. The test results represent that the atmosphere of the restaurant will certainly have a positive significance on customer satisfaction, with a t value of 2.615. Product quality will certainly have a positive significance on customer satisfaction, with the result t count 5,883. Lifestyle will certainly have a positive significance on customer satisfaction, with the result t count 2.469. Then simultaneously the atmosphere of the restaurant, product quality and lifestyle will certainly be able to have an influence on Panda Hotpot and Grill customer satisfaction by 62.5% according to the coefficient of determination data (R2). Based on these test results it can be concluded that the restaurant atmosphere will certainly be able to give a positive and significant impact, product quality will have a positive and significant impact and lifestyle will certainly be able to provide a positive and significant impact and simultaneously the restaurant atmosphere, product quality and lifestyle will certainly be able to give a positive and significant influence on customer satisfaction Panda Hotpot and Grill